Treatment of genu varum in medial compartment osteoarthritis of the knee using the Ilizarov method - Catagni, M.A.; Guerreschi, F.; Ahmad, T.S.; Cattaneo, R. (Elsevier, 1994)
The high tibial osteotomy has been used to treat medial compartment osteoarthritis for many years and has stood the test of time as an effective method for treatment of the varus knee in this condition. This article presents a quick, simple, safe, and effective method of doing this operation through small incisions using the Ilizarov apparatus